Effects of acupotomy on the activity of osteoclasts and osteoblasts in the subchondral bone of rabbits with early and mid-stage knee osteoarthritis models - Mira Lee; Yan Guo; Xilin Chen; Longfei Xing; Wei Zhang; Lia Chang; Changqing Guo (Journal of Traditional Chinese Medical Sciences, 2023)
Objective: To investigate whether acupotomy could inhibit subchondral bone remodeling in knee osteoarthritis (KOA) rabbits by regulating the activity of osteoblasts and osteoclasts. Methods: KOA rabbits were prepared by immobilization for 6 and 9 weeks by Videman method. Nine groups of rabbits (control, 6 weeks and 9 weeks model, 6 weeks and 9 weeks acupotomy, 6 weeks and 9 weeks electroacupuncture, and 6 weeks and 9 weeks drug groups) received acupotomy, electroacupuncture and risedronate sodium intervention, respectively, for 3 weeks. Results: Acupotomy can inhibit the activity of osteoclasts and osteoblasts in subchondral bone by reducing the proteins expression of cathepsin K (CK) and tartrate-resistant acid phosphatase (TRAP) and decreasing the proteins expression of osteocalcin (OCN) and alkaline phosphatase (ALP), to intercept the abnormal bone resorption and bone formation of subchondral bone in 6-week and 9-week immobilization-induced KOA rabbits. Conclusion: These findings indicated that acupotomy may be more advantageous than risedronate sodium intervention in modulating subchondral bone remodeling in KOA rabbits, especially in 9-week immobilization-induced KOA rabbits.